PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN ALOKASI DANA DESA DI DESA LIWUTUNG II KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - LENGKEY, SELVIANA EMELINIA; Lengkong, florence Daicy; ROMPAS, Sonny (Sam Ratulangi University, 2016)
ABSTRACT: Empowering communities in the utilization of the Village Fund Allocation in Liwutung IIvillage sub district Pasan, Southeast Minahasa. Purpose of this study is to know about budget allocation inthe village and how to utilize it, also to know the challenge and opportunity in community empowering.The method of this study is qualitative. The data in the study are primer and secondary. The technic of thestudy are observation, interview and collect some photos of those activities. The data were collect from severalresource and analysis.Result of the study is showing that budget utilizing in Liwutung II village was not going through as rules oflocal government as budget fund utilizing manual. 30% budget allocation is for village operational and 70%is for community development, but the 70% is still not utilize for community empowering.Keywords: Community Empowering, the utilization of the Village Fund Allocation